PENGARUH KADAR PEREKAT DAN CAMPURAN KULIT TERHADAP SIFAT FISIS DAN MEKANIS PAPAN PARTIKEL TUSAM (Pinus merkusii) - I M Sulastiningsih; Rozak Memed; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The laboratory test of strength properties of pine particleboard subtituted with 0, 20, 40 and 60 percent of pine bark, glued with 8, 10, and 12 percent liquid urea formaldehvde (by particle dry weight basis) is reported in this paper. Pine wood and its bark were obtained from West Java. The result shows that the substitution with bark of 20, 40, and 60 percent of pine wood particle improved water absorption and thickness- swelling properties; however, it decreased mechanical properties of particleboard. Particleboard with high bark content has lower mechanical properties than that with low bark content. The physical and mechanical properties of particleboard that is subtiuuted with 20 and 40% bark and 10 and 12% urea-formaldehyde resin meet the FAO standard for medium density particleboard, except for, modulus of rupture. If we compared with Indonesian standard, the properties that do not meet the standard are the modulus of rupture and the internal bond strength